Widerstand und Biografie: Die widerständige Praxis der Prager Journalistin Milena Jesenská gegen den Nationalsozialismus - Darowska, Lucyna (transcript, 2014)
How did Milena Jesenská become a member of the resistance? This question is at the heart of Lucyna Darowska's investigation, which unlocks new perspectives in interpretive biographical research within politico-historical research into the resistance to National Socialism. Beginning with New Historicism, she critically engages with various theoretical approaches in an interdisciplinary fashion, in order to approach an understanding of the motivations behind acts of resistance. Using a methodological and theoretical basis that is fitted to the object of research, she develops interpretations of acts of resistance against the Nazi regime by the Prague journalist Milena Jesenská.Research on Milena Jesensk began late, since she was mainly known amongst Western European readers as the anonymous addressee of Franz Kafka's letters. As a critic of communism, in Czechoslovakia she was veiled in silence. The first international conference on Milena Jesensk, which took place in Prague from 20-21 October 2014, showed that the previous biographical works and the international discourse on Milena Jesensk has met with extraordinary interest, and that the intensification of the research on her is urgently required. At the center of this lies both her extensive oeuvre as well as various aspects of her biography. One of the most interesting questions in Milena Jesensk's biography, which transcends research into any one individual, is the question of her resistance. She can be identified at multiple points in her biography with a staunchly resistant position, against national socialism, and from 1936, against communism, which sets Jesensk apart from so many of her contemporaries. Last but not least, the methodological questions around biographical analysis are tightly knitted together with the motivations for the practice of resistance.